Barriers and facilitators of household provision of dairy and plant-based dairy alternatives in families with preschool-age children. Issue 17 (19th December 2021) - Laila, Amar; Topakas, Nicole; Farr, Emily; Haines, Jess; Ma, David WL; Newton, Genevieve; Buchholz, Andrea C
Abstract: Objective: This study aimed to explore barriers and facilitators of the provision of dairy and plant-based dairy alternatives (PBDA) by parents of preschool-age children, a previously unexplored area of research. Design: Five focus groups of parents were conducted and audio-recorded. Verbatim transcripts were analysed using thematic analysis. Setting: University of Guelph, in Guelph, ON, Canada in 2019. Participants: Thirty-two ( n 19 mothers, 13 fathers) parents of preschool-age children. Most (59 %) were university or college educated. Results: Facilitators common to both dairy and PBDA provision included perceived nutritional benefits, such as dairy's Ca, protein and fat content, and PBDA's protein content, and the perception that PBDA adds variety to the diet. Facilitators unique to dairy v. PBDA provision included the taste of, familiarity with, and greater variety and accessibility of dairy products, specifically child-friendly products. A facilitator unique to PBDA v . dairy provision was ethical concerns regarding dairy farming practices. Barriers common to both dairy and PBDA provision included perceived cost, concerns regarding the environmental impact of production, and high sugar content. Barriers specific to dairy included use of antibiotics and hormones in dairy production. A barrier specific to PBDA was the use of pesticides. Conclusion: Behaviour change messages targeting parents of preschoolers can emphasise the nutrition non-equivalence of dairy and some PBDA and can educate parents on sources of affordable, unsweetened dairy and PBDA.